Penerapan Metode Activated Sludge dalam Pengolahan Limbah Cair Industri Tahu Beru - Husni Zaini Abdul Gani; Bagyo Yanuwiadi; Arief Rachmansyah (Dinamika Lingkungan Indonesia, 2022)
The tofu industry in its production process uses ± 25 liters of water per 1 kg of soybean raw material. Soybean used as raw material for tofu contains protein, carbohydrates, fat, and other nutritional ingredients so that the resulting liquid waste contains high organic matter that has the potential to pollute the environment with a value of Biological Oxygen Demand (BOD) of 467 mg/L and Chemical Oxygen Demand (COD) of 668.2 mg/L. Efforts to control water pollution can be overcome by processing biotechnology using an activated sludge system. This study aims to analyze the effectiveness of polluted water sediment as the main ingredient of activated sludge in reducing levels of Biological Oxygen Demand (BOD) and Chemical Oxygen Demand (COD) and to determine the growth rate of microorganisms in the acclimatization process. This research was carried out on 4 different composition variations in batches under aerobic conditions using an aerator and a pump as a stirrer. The results showed that the composition of the sludge in treatment IV, namely the composition of the sludge consisting of (60% Waste, 40% Nutrients, and cultured RPH sludge) was the best composition at 60 hours of aeration with the effectiveness of removing BOD concentration of 90.10% and COD concentration. amounted to 87.41% or achieved a reduction value of 46.21 mg/L of BOD concentration and 84.14 mg/L of COD concentration with a specific biomass growth rate of 0.054 day-1.